PENGARUH PENGGUNAAN BERBAGAI JENIS LITTER TERHADAP BOBOT HIDUP, KARKAS, GIBLET, DAN LEMAK ABDOMINAL BROILER FASE FINISHER DI CLOSED HOUSE - Tri Haryanto Saputraa; Khaira Nova; Dian Septinova (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2015)
Closed house is a broiler chicken coop design that there is no environmental effect or that minimized of outer interference. The right choose of litter on broiler cultivation at closed house could give the comfortable condition for broiler productivity. Those condition will be give impact to carcass giblet and abdominal fat productivity. The purpose of the research are: (1) to know the effect of the kind of litter to live weight, carcass, giblet, and abdominal fat of broiler at closed house, (2) to know the best of litter that give effect to live wight, carcass, giblet, and abdominal fat of broiler at closed house. The research was done on April 15th 2014 until May 10th 2014 at PT. Rama Jaya Lampung closed house Sidorejo hamlet, Krawang Sari village, district Natar, South Lampung regency. The broiler that used in this research is broiler strain CP707. The research method use complete randomize block design with 3 treatments : P1: ricehusk litter, P2: wood shavings litter, P3: ricestraw litter, with 6 times replication. The research data’s were analyzed by using 5% of Analysis of variance test. If there is significant effect on the variable, the test will be continue by Duncan test. The observed variable were live weight, carcass weight, giblet weight, and abdominal fat weight. The result shown that: (1) rice husk litter, wood shavings litter and rice-straw litter have no significant effect (P>0,05) toward live weight, carcass weight, giblet weight, and abdominal fat weight of broiler finisher phase at closed house , and (2) the used of three kind of litter were give same result toward live weight, carcass weight, giblet weight, and abdominal fat weight of broiler finisher phase at closed house.